Evidence for purchasing power parity under the current float : economic applications using panel data unit root test. - Lim, Siew Ming. (2008)
This paper contributes to the resolution of the debate on PPP. It revisits long run equilibrium PPP under the current float for the period 1973-1998, using panel data unit root test analysis. We examine the existence of PPP with respect to openness. Evidence has shown that PPP holds in the long run for both open and closed economies, although the former exhibits a stronger case for PPP. We further evaluate PPP based on region, the stage of economic development, as well as the rate of growth of income per capita. Having done so, we compare the results to conclude that there is a faster convergence to long run equilibrium PPP for the richer, relatively open economies; or in short the more developed economies. We also confirm the existence of the Balassa-Samuelson effect. In a more general sense, empirical evidence shows that the use of wholesale price indices, rather than consumer price indices, can bring about a faster reversion to PPP.